Road safety analysis of the BR-020 road inserted in the Distrito Federal (Research, Society and Development, 2021)
This article focus on analysing the traffic safety at a BR-020 segment, located in Distrito Federal. To achieve this goal, the highway, accident types and causes were characterized. Using the accidents data provided by the Federal Highway Police Department, it was possible to georeference them. Three methods that identify critical segments were applied to the highway: DNIT methodology, Ministry of Transportation methodology and Meneses’ methodology. After comparing the results from each methodology, flaws were found within each method, being the Meneses technique the most complete. Upon studying the critical highway segments, defective points were identified and improvements were suggested.